Immunolocalisation and imaging of small cell cancer xenografts by the IgG2a monoclonal antibody SWA11. - Smith, A. (Nature Publishing Group, 1989)
We describe here a murine monoclonal antibody of the IgG2a isotype which was generated against the SW2 human small cell carcinoma cell line. The antibody, SWA11, was shown to bind to a partially defined antigen preferentially expressed on cell lines of small cell carcinoma origin. In vitro binding studies revealed 6.1 x 10(5) antigenic sites on the SW2 cell line and the Ka to be 1.2 x 10(9)M-1. Following injection into mice bearing 1-2 cm3 SW2 xenografts, SWA11 showed strong selective accumulation in the small cell heterotransplants with a tumour to blood ratio of 7.5:1 at day 4. Other tumour to organ ratios were similarly high at 19:1, 22:1 and 12:1 for liver, kidney and spleen respectively. The absolute amount of SWA11 which localised was 10.5% of total injected material per gram tumour at day 2 and this level did not markedly decrease by day 4. The high ability of SWA11 to localise to SCC xenografts was confirmed by external gamma scintigraphy. The potential application of SWA11 as a model system for in vivo radioimmunotherapy is discussed. IMAGES: